Business responses to climate change in developing countries : strategies for reducing greenhouse gas emissions in Vietnam - Hoang Duc Binh; Do, Ba Khang; Badir, Yuosre; Islam, Nazrul; Vilas Nitivattanon; Hoa Sen University, Vietnam; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
Research regarding business reactions to climate change have attracted scholarly interest in recent years. With only a few exceptions, these studies have mainly centered around global corporations from industrialized nations using voluntarily disclosed data through international initiatives. Despite the vast literature on firms' behavior towards climate change, study on how firms in developing nations react to this critical issue is lacking. This research objective is to identify emergent climate change strategies and its response patterns implemented by businesses in developing nations toward their carbon reductions. In light of existing firm response classifications, a framework for assessing carbon reduction activities for a developing economy was established. Utilizing this instrument, a study involving the responsible parties on climate change or environment was performed. Information gathered from 185 FDI and local companies in Vietnam was analyzed using an exploratory factor analysis (EF A) technique to classify carbon strategic options of firms. Cluster analysis was then carried out based on factor scores, the results of factor analysis, to identify patterns in firm responses. The EF A identified four distinct carbon reduction strategies compared to eight strategies with the original framework, each of which may be measured in five profile categories: pro-active, active, emerging, beginner and indifferent. Even though many businesses fell into the last two profiles (i.e., beginner and indifferent), those were aware of climate change issues had adopted several strategies, such as admission transferring and trading, process improvement, information and self-regulation, and product development towards reducing greenhouse gas emissions. Multinational firms adopt several carbon reduction activities with higher mean values than those of local companies. Most of the active and pro-active firms are large firms from United States, Europe and Japan.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Management, School of Management
Thesis (Ph.D.) - Asian Institute of Technology, 2017
Keywords: Climatic changes -- Developed countries; Climatic changes -- Economic aspects -- Vietnam; Climatic changes -- Environmental aspects -- Vietnam